Peningkatan Ekonomi Melalui Pemberdayaan Dan Pelatihan Kerajinan Sampah Anorganik Plastik - Pristi Sukmasetya; Aditya Prasetyawan; Reza Pradana Adiharsa; Annisa Shabilla (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2020)
Garbage has become a common problem in every environment, both urban and rural environments. Inorganic waste cannot be degraded by nature so it can have a bad impact if not managed. One thing that must be done to overcome the increase in waste volume is to manage waste through community participation. The program on community participation-based waste management was conducted in Tirto Hamlet located in Paremono Village, Mungkid District, Magelang District. This research aims to find out how the process of managing waste into a creative product, the creation of plastic waste that has economic value so that it can increase the income of the community in Tirto Hamlet. Approached method that have been used is descriptive qualitative, a study that intends to describe the phenomena that occur at the study site. Data collection techniques include interviews, observation, and documentation. Based on the results of the study, the form of community participation in the management of inorganic waste is to recycle (recycle) plastic waste into handicrafts in the form of bags that have a selling power that can generate profits.